Paroxysmal Autonomic Instability with Dystonia Syndrome in Association with Wolf–Hirschhorn Syndrome - Manalo, Rachel; Contreras, Marioxy; Gorla, Sudheer R.; Sokoloski, Mary C.; Kardon, Richard E. (Journal of Pediatric Neurology, 2019)
Paroxysmal autonomic instability with dystonia (PAID) syndrome, a distinct entity of autonomic dysfunction, is typically seen following acute brain injury. There are no reported cases of this entity in association with Wolf–Hirschhorn syndrome (WHS). Here, we report a case of WHS whose predominant neurological manifestations were consistent with PAID syndrome.
Keywords: Wolf–Hirschhorn syndrome; PAID syndrome; beta blockers